X-ray fluorescence mapping as a first-hand tool in disseminated ore assessment: sandstone-hosted U–Zr mineralization. (September 2019) - Mikysek, Petr; Trojek, Tomáš; Mészárosová, Noemi; Adamovič, Jiří; Slobodník, Marek
Graphical abstract: Highlights: Abilities of a unique XRF analyzer for study of low-grade U-sandstone were tested. Distributions of U–Zr and other elements were observed in large natural samples. Correlations were used for verification of geochemical coherence among elements. Abstract: Analytical capabilities of X-ray fluorescence for 2-dimensional elemental analysis were tested on worldwide-unique sandstone-hosted U–Zr mineralization (Bohemian Cretaceous Basin, Czech Republic), and combined with measured spectral data. The applied approach was aimed at the detection of uranium and zirconium, visualization of their distribution across mineralized lithological units and description of their relationships with associated elements (As, Fe, Nb, Pb, Sr, Ti). The studied samples were low-grade uranium-bearing sediments. Experimental work employed laboratory 2D scanning X-ray fluorescence analyzer with the gold target Mini-X X-ray tube. Maps of U–Zr and other identified elements demonstrated their patchy distribution and a frequent association of the elements with mineral fillings (clay matrix, organic matter or Fe sulfides). A correlation-based analysis was used to verify geochemical coherence between the measured elements. This showed an extremely strong linear dependence (R ≥ 0.90) between U and Zr. In addition, a strong correlation (R ≥ 0.85) between U–Zr and some associated elements (As, Nb ± Fe, Pb, Sr) was confirmed. The efficiency and the limits of X-ray fluorescence mapping were tested by comparison with high-resolution techniques. Non-destructive mapping of large natural samples provided relevant data for further mineralogical study with respect to rapid pre-concentration of the ore material.